WHAT ANATOMIC FEATURES GOVERN PERSONAL LONG-TERM HEALTH RISKS FROM BREAST CANCER RADIOTHERAPY? - Kundrát, Pavel; Simonetto, Cristoforo; Eidemüller, Markus; Remmele, Julia; Rennau, Hannes; Sebb, Sabine; Wolf, Ulrich; Hildebrandt, Guido (Radiation protection dosimetry, 2019)
Breast cancer radiotherapy may in the long term lead to radiation-induced secondary cancer or heart disease. These health risks hugely vary among patients, partially due to anatomy-driven differences in doses deposited to the heart, ipsilateral lung and contralateral breast. We identify four anatomic features that largely cover these dosimetric variations to enable personalized risk estimates. For three exemplary, very different risk scenarios, the given parameter set reproduces 63-74% of the individual risk variability for left-sided breast cancer patients. These anatomic features will be used in the PASSOS software to support decision processes in breast-cancer therapy.
Keywords: plíce; srdce; Tomography, X-Ray Computed; nádory prsu; radiační poranění; Humans; Image Processing, Computer-Assisted; Radiotherapy Dosage; kritické orgány; prsy; Breast Neoplasms; celková dávka radioterapie; Neoplasms, Radiation-Induced; Radiation Injuries; nádory vyvolané zářením; Radiotherapy Planning, Computer-Assisted; plánování radioterapie pomocí počítače; Heart; Lung; radioterapie s modulovanou intenzitou; Breast; počítačové zpracování obrazu; ženské pohlaví; lidé; počítačová rentgenová tomografie; Organs at Risk; Radiotherapy, Intensity-Modulated; Female